Pelatihan Khatib dan Bilal bagi Mahasiswa Prodi Ilmu al-Qur’an dan Tafsir Fakultas Ilmu Agama Islam Universitas Islam Indragiri - Ridhoul Wahidi; Syafril Syafril; Amaruddin Amaruddin; Nasrullah Nasrullah; Fiddian Khairudin (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Indragiri (UNISI), 2023)
Khatib and bilal training for students is important in community service activities. This concerns the function of the sermon and bilal which is very important as part of the Islamic da'wah. To find answers to the importance of this activity, preacher and bilal training was held for students of the Islamic Religious Sciences faculty at Indragiri Islamic University. The aim of this PkM activity is first, to provide students with material about khatib and bilal. Second, equip students to understand the terms and conditions of the sermon. The problem solving carried out by PkM activities in the form of implementing this training activity is an explanation of the bilal reading material, the first and second preacher readings, and an introduction to the requirements and pillars of the khatib along with the history of Friday prayers. then practical activities of khatib and bilal for students.